L’effetto delle operazioni di fusione e acquisizione sui profitti degli azionisti nell’industria farmaceutica - Skrepnek, Grant H.; Lawson, Kenneth A. (Farmeconomia. Health Economics and Therapeutic Pathways, 2001)
The purpose of this study was to quantify the excess return in shareholder security prices following initial announcements of successful horizontal pharmaceutical mergers which occurred between 1985 and 1996. An event study methodology was used to study a sample of26 fim1s involved in 14 mergers wherein transaction costs exceeded 500 million. Overall, results of the study were consistent with prior research, indicating that target-firm shareholders received a majority oft he short-term merger-related wealth effects in comparison to those received by bidder- firm shareholders.